Blotting Out the Name, Part 2: Scribal Methods of Erasing the Tetragrammaton in Medieval Hebrew Bible Manuscripts - Gordon, Nehemia (Textus, 2020)
Part 1 of this study considered how the rabbinic prohibition against erasing the Tetragrammaton led to scribes performing diverse procedures to resolve scribal errors. In part 2 it will be shown that special procedures were performed in Torah scrolls, namely, skiving, excision, and removing sheets. Washing off the divine name was not found in the corpus examined. Despite the rabbinic prohibition, medieval Jewish scribes occasionally marked the Tetragrammaton with a strikethrough or erased it through abrasion. This may have been the handiwork of Karaite scribes who did not see themselves bound by the midrashic interpretation of Deut 12:4. The scribes who wrote the Aleppo Codex may have abraded erroneous instances of the Tetragrammaton in order to create a model codex. Scribes in the isolated Jewish community of Kaifeng, who erased erroneous instances of the Tetragrammaton, may not have been familiar with rabbinic strictures.